Meningkatkan Kemampuan Kerjasama melalui Permainan Menyusun Puzzle pada Anak Usia 5-6 Tahun di TK Kenanga Raya - Farida, Niken; Siregar, Sakinah; Tamba, Sardiama (STAI Auliaurrasyidin Tembilahan, 2022)
Cooperation is the ability to work together to complete a task with others. The process of working together children are trained to be able to suppress individual personalities and prioritize group interests. Children's learning activities at Kenanga Raya Kindergarten on the ability to cooperate are still not developed. Based on my observations, it shows that children still like to play alone and do not want to play with other friends. This study aims to improve children's cooperation skills through puzzle games at Kenanga Raya Kindergarten Medan. The subjects used in this study were group B children aged 5-6 years, totaling 9 children. Data collection is done by direct observation, performance, and documentation. Based on the results of the study, it was found that the improvement of children's cooperative skills through group B puzzle games at Kenanga Raya Kindergarten Medan in the 2020/2021 academic year. This can be proven by the pre-cycle results of 25%, 52,2% in the first cycle and increased to 86% in the second cycle. So it can be concluded that puzzle games improve the cooperative ability of group B children in Kenanga Raya Kindergarten Medan.